Mineral reactivity determines root effects on soil organic carbon - Liang, Guopeng; Stark, John; Waring, Bonnie Grace (Nature communications, 2023)
Modern conceptual models of soil organic carbon (SOC) cycling focus heavily on the microbe-mineral interactions that regulate C stabilization. However, the formation of ‘stable’ (i.e. slowly cycling) soil organic matter, which consists mainly of microbial residues associated with mineral surfaces, is inextricably linked to C loss through microbial respiration. Therefore, what is the net impact of microbial metabolism on the total quantity of C held in the soil? To address this question, we constructed artificial root-soil systems to identify controls on C cycling across the plant-microbe-mineral continuum, simultaneously quantifying the formation of mineral-associated C and SOC losses to respiration. Here we show that root exudates and minerals interacted to regulate these processes: while roots stimulated respiratory C losses and depleted mineral-associated C pools in low-activity clays, root exudates triggered formation of stable C in high-activity clays. Moreover, we observed a positive correlation between the formation of mineral-associated C and respiration. This suggests that the growth of slow-cycling C pools comes at the expense of C loss from the system. Root exudates can either promote or impede the formation of stable, mineral-associated soil organic carbon (MAOC). Yet, carbon stabilisation in MAOC is decoupled from changes in the total soil carbon pool, i.e., carbon sequestration.